The role of melatonin in plant growth and metabolism, and its interplay with nitric oxide and auxin in plants under different types of abiotic stress - Ahmad, Irshad; Song, Xudong; Hussein Ibrahim, Muhi Eldeen; Jamal, Yousaf; Younas, Muhammad Usama; Zhu, Guanglong; Zhou, Guisheng; Adam Ali, Adam Yousif (Frontiers in Plant Science, 2023)
Melatonin is a pleiotropic signaling molecule that reduces the adverse effects of abiotic stresses, and enhances the growth and physiological function of many plant species. Several recent studies have demonstrated the pivotal role of melatonin in plant functions, specifically its regulation of crop growth and yield. However, a comprehensive understanding of melatonin, which regulates crop growth and yield under abiotic stress conditions, is not yet available. This review focuses on the progress of research on the biosynthesis, distribution, and metabolism of melatonin, and its multiple complex functions in plants and its role in the mechanisms of metabolism regulation in plants grown under abiotic stresses. In this review, we focused on the pivotal role of melatonin in the enhancement of plant growth and regulation of crop yield, and elucidated its interactions with nitric oxide (NO) and auxin (IAA, indole-3-acetic acid) when plants are grown under various abiotic stresses. The present review revealed that the endogenousapplication of melatonin to plants, and its interactions with NO and IAA, enhanced plant growth and yield under various abiotic stresses. The interaction of melatonin with NO regulated plant morphophysiological and biochemical activities, mediated by the G protein-coupled receptor and synthesis genes. The interaction of melatonin with IAA enhanced plant growth and physiological function by increasing the levels of IAA, synthesis, and polar transport. Our aim was to provide a comprehensive review of the performance of melatonin under various abiotic stresses, and, therefore, further explicate the mechanisms that plant hormones use to regulate plant growth and yield under abiotic stresses.